2022
DOI: 10.1155/2022/9979200
|View full text |Cite|
|
Sign up to set email alerts
|

A Potential Prognostic Biomarker for Glioma: Aldo-Keto Reductase Family 1 Member B1

Abstract: Aldo-keto reductase family 1 member B1 (AKR1B1) plays a vital role in tumor development and is involved in the tumor immune process. However, its role in glioma cell is poorly studied. This study’s aim was to assess the role of AKR1B1 in glioma through bioinformatics analysis. The AKR1B1 expression data and corresponding clinical data of glioma were collected from the Cancer Genome Atlas (TCGA) database. The R packages were used for data integration, extraction, analysis, and visualization. According to the me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
See 1 more Smart Citation
“…This article has been retracted by Hindawi following an investigation undertaken by the publisher [ 1 ]. This investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process: Discrepancies in scope Discrepancies in the description of the research reported Discrepancies between the availability of data and the research described Inappropriate citations Incoherent, meaningless and/or irrelevant content included in the article Peer-review manipulation …”
mentioning
confidence: 99%
“…Tis article has been retracted by Hindawi following an investigation undertaken by the publisher [1]. Tis investigation has uncovered evidence of one or more of the following indicators of systematic manipulation of the publication process:…”
mentioning
confidence: 99%